PERENCANAAN STRUKTUR GEDUNG PARKIR MOTOR TIGA LANTAI UNIVERSITAS MUHAMMADIYAH SEMARANG MENGGUNAKAN ETABS - Meilinda Dewi Astuti; Fuad Zuhair; Akmalul Anam; Farell Adzar Aldante (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The growth of academic activities within the university environment has led to an increased demand for parking facilities, particularly for two-wheeled vehicles. Limited parking space can result in vehicle congestion, disorganized parking, and disruptions to vehicle and pedestrian circulation on campus. Designing a multi-story parking building offers an alternative to increase parking capacity while optimizing land use. This study aims to design the structure of a three-story motorcycle parking building at Universitas Muhammadiyah Semarang using a reinforced concrete structural system and to analyze the structural response to gravity and seismic loads using ETABS software. The building is designed with dimensions of 24.00 m × 20.00 m and an inter-story height of 3.20 m, utilizing concrete with a compressive strength (f'c) of 25 MPa and reinforcement steel with a yield strength (fy) of 420 MPa. The resulting parking capacity is 119 motorcycles on the first floor and 101 motorcycles each on the second and third floors, bringing the total capacity to 321 units. Seismic analysis was conducted using the Response Spectrum method. Evaluation results indicate a maximum inelastic drift of 12.084 mm in the X-direction and 15.285 mm in the Y-direction, well within the allowable drift limit of 49.231 mm. All checks yielded satisfactory results. Thus, the designed structure meets the requirements for strength, stiffness, and stability based on the applicable design standards.